KARAKTERISTIK ADJEKTIVA DALAM IKLAN MAJALAH GOGIRL! - Syafriani, Sinta; Agustina, Agustina; Ngusman, Ngusman (Jurnal Bahasa dan Sastra, 2018)
The purpose of this study is to describe: (1) the form of adjectives and (2) the level (level) adjectives in the ad magazine Gogirl !. This research type is qualitative research by using descriptive method. The data of this research are sentences containing the element of adjective in the advertisement of Gogirl! Magazine. The source of this research data is Gogirl magazine! as many as 13 magazines. Data were collected by: (1) observing the data and (2) identifying the data. Data analysis is done by: (1) classifying data, (2) analyzing and interpreting data based on the theory used and (3) summarizing the data. Based on the data analysis found two research results. First, we find two forms of adjectives in Gogirl! Magazine ads, namely (1) basic adjectives and (2) derived adjectives, ie (a) baffled adjectives consisting of prefixes and suffixes, (b) repeated reduplication (dwilingga), (c) multiple adjectives, combination of two free morphemes, and (d) class displacement injections in the form of deverbalization adjectives. Second, there are four levels of adjectives, namely (1) positive level, marked with tipis, tinggi, bagus, pas; (2) the comparative level, characterized by a lebih mulus, lebih cerah, lebih aman, lebih tebal; (3) superlative level, marked terkecil, terbaru, terdekat, paling sehat; and (4) excessive levels, marked by the word ketagihan, keharuman mewah, super lengkap, maksimal.Keywords: adjectives, forms, levels, advertisement.